The Church in Exile God's Counter Culture in a Non-Christian World - Thompson, James (Abilene Christian University Press, 1990)
Christians have become more and more a minority group in American culture, and so now find themselves in a situation similar to the early Christians-facing the challenge of living as cultural exiles. The Church in Exile draws upon the epistle of 1 Peter, which was written to "exiles," to help us learn how to live faithfully when many around us do not share Christian values.